2021
DOI: 10.3390/microorganisms9051050
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ionizing Radiation on the Bacterial and Fungal Endophytes of the Halophytic Plant Kalidium schrenkianum

Abstract: Endophytic bacteria and fungi colonize plants that grow in various types of terrestrial and aquatic ecosystems. Our study investigates the communities of endophytic bacteria and fungi of halophyte Kalidium schrenkianum growing in stressed habitats with ionizing radiation. The geochemical factors and radiation (at low, medium, high level and control) both affected the structure of endophytic communities. The bacterial class Actinobacteria and the fungal class Dothideomycetes predominated the endophytic communit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 59 publications
(66 reference statements)
1
11
0
Order By: Relevance
“…The findings of this study agree with those reported in our previous study. Specifically, a higher diversity of bacterial communities in the roots than in aerial tissues and more radiation-sensitive fungal communities than bacterial communities were also observed in our previous study ( Zhu et al, 2021 ). In previous study, bacterial plant microbiome commonly showed similar patterns that higher diversity in roots than in aerial tissues, whereas the fungal diversity is no always higher in aerial tissues ( Su et al, 2010 ; Gdanetz and Trail, 2017 ).…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…The findings of this study agree with those reported in our previous study. Specifically, a higher diversity of bacterial communities in the roots than in aerial tissues and more radiation-sensitive fungal communities than bacterial communities were also observed in our previous study ( Zhu et al, 2021 ). In previous study, bacterial plant microbiome commonly showed similar patterns that higher diversity in roots than in aerial tissues, whereas the fungal diversity is no always higher in aerial tissues ( Su et al, 2010 ; Gdanetz and Trail, 2017 ).…”
Section: Discussionsupporting
confidence: 84%
“…The bacterial and fungal taxa were determined using the pipeline described by Zhu et al (2021) . The bacterial and fungal ASVs were first identified using Naïve Bayes approach with a minimum of 75 bootstrap calls following DADA2 workflow ( Callahan et al, 2016 ) against SILVA version 132 ( Quast et al, 2013 ) and UNITE general FASTA release for Fungi version 8.0 ( Nilsson et al, 2019 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although root endophytic microbiota is more determinant than soil microorganisms, the extent to which root fungi influence the microbial community assembly is not clear as such studies are quite challenging [132]. Therefore, it is still undetermined the real impact of the new biocontrol methods on the microbiota of soils and plant roots [133] and a consensus on best practices in microbiome research is still missing [134], [135].…”
Section: Discussionmentioning
confidence: 99%